2011
DOI: 10.1007/s13193-011-0072-8
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Negative Breast Cancer in India: Do We Really Have Higher Burden of this Subtype?

Abstract: ER negative and Triple negative breast cancers carry a poorer prognosis and are not amenable to hormone therapy. It has been previously observed that Indian patients with breast cancer have a higher tendency to have these tumours. Whether this is due to inherent biological differences in the tumours of our patients is a matter of much debate. We have analysed 250 patients of breast cancer for hormone receptor status, compared them with western series, and attempted to support the hypothesis that the higher ER … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 10 publications
5
19
0
Order By: Relevance
“…Data from earlier studies conducted in India reveal a higher proportion of ERnegative breast cancers when compared to the US or Western Europe; the reasons for this are several - technical failures, younger age of patients, and a higher grade or advanced stage at presentation [8-13]. In our study, the overall ERpositivity was found to be 52.0%.…”
Section: Discussionsupporting
confidence: 45%
“…Data from earlier studies conducted in India reveal a higher proportion of ERnegative breast cancers when compared to the US or Western Europe; the reasons for this are several - technical failures, younger age of patients, and a higher grade or advanced stage at presentation [8-13]. In our study, the overall ERpositivity was found to be 52.0%.…”
Section: Discussionsupporting
confidence: 45%
“…One of the important issues is the occurrence of estrogen receptor negative (ER-) BC at earlier ages in LMICs [31] . It has been suggested that the younger age of BC in LMICs is due to the age distribution of the population [31] , although there is a possibility that the aggressive ER-BC seen in younger ages in LMICs might be a different disease subtype, as has been suggested in Asia and Africa [32,33] .…”
Section: Dey S Breast Cancer Prevention In Lmicsmentioning
confidence: 98%
“…The best characterized of these subtypes are luminal A, luminal B, HER2, and basallike carcinoma. Immuno-phenotyping with ER, PR, and HER2 biomarkers can be used as a surrogate for molecular category of breast cancer (13)(14)(15). Luminal sub-group constitutes approximately 70% of invasive breast cancers.…”
Section: Association Of 25-oh Vitamin D Levels With Breast Cancer Patmentioning
confidence: 99%
“…Estrogen receptor negativity is one of the poor prognostic indicators in breast cancer (13). The antiproliferative action of vitamin D in breast cancer could partly be mediated by its role in down-regulating estrogen receptor abundance in breast cancer (7,11).…”
Section: Association Of 25-oh Vitamin D Levels With Breast Cancer Patmentioning
confidence: 99%